1984
DOI: 10.1002/hep.1840040216
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Bone Disease in Alcoholic Cirrhosis: A Comparison of the Effect of Vitamin D225-Hydroxyvitamin D, or Supportive Treatment

Abstract: In a study of 56 alcoholics with liver cirrhosis, 18 (32%) had decreased bone density and low levels of serum 25-hydroxyvitamin D (25-OH-D) (less than 20 ng per ml). To compare the efficacy of vitamin D2 and 25-OH-D treatment in correcting the metabolic bone disease in alcoholic cirrhosis, the 18 patients were randomized in the following manner, in groups of six patients each: Group 1, control (received no supplemental vitamin D treatment); Group 2, given vitamin D2 (50,000 IU p.o.) two to three times weekly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 27 publications
2
25
0
3
Order By: Relevance
“…Furthermore, vitamin D has been shown to be protective against falls, thus reducing fracture risk further [10]. Our observations are supported by a number of previous studies which have demonstrated an association between chronic alcoholism and low circulating levels of vitamin D [3,12]. Our findings therefore show that in alcoholic women increasing dietary vitamin D levels, in addition to calcium, is an important potential health intervention to reduce fracture risk.…”
Section: Study Findingssupporting
confidence: 87%
“…Furthermore, vitamin D has been shown to be protective against falls, thus reducing fracture risk further [10]. Our observations are supported by a number of previous studies which have demonstrated an association between chronic alcoholism and low circulating levels of vitamin D [3,12]. Our findings therefore show that in alcoholic women increasing dietary vitamin D levels, in addition to calcium, is an important potential health intervention to reduce fracture risk.…”
Section: Study Findingssupporting
confidence: 87%
“…Low vitamin D levels have also been reported in a third of alcoholics with a low BMD, and vitamin D supplementation has been shown in one study to improve BMD at the wrist in some patients. 7 Longstanding hypogonadism in men is associated with reduced bone remodeling and decreased bone formation, which is reversible with adequate hormonal replacement. Hypogonadism as measured by free testosterone levels has been reported to occur in up to 75% of patients with cirrhosis needing transplantation but is unrelated to the etiology of the cirrhosis.…”
Section: Osteoporosismentioning
confidence: 99%
“…Posttransplant bone biopsies have shown that tacrolimus-treated patents have an earlier recovery of bone metabolism and trabecular bone structure than those taking cyclosporine, but their effect on early bone loss remains unclear. 7 The cumulative steroid dose has been implicated in impairing bone formation in these first few months, and a change in practice with lower steroid usage after transplantation probably explains the fall in fracture frequency observed anecdotally over the last decade and supported by the publication of Guichelaar et al 23 in this month's issue of HEPATOLOGY.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…In contrast, a study conducted in 18 men with alcoholic cirrhosis showed that patients treated with vitamin D2 (50,000 IU, 2-3 times/week) or 25-hydroxy-vitamin D (20-50 mg/ day) for an average of 11 months exhibited significantly improved lumbar mineral density (50). Therefore, although there are no data confirming its efficacy against bone loss, calcium and vitamin D supplementation is recommended in patients with CLD at daily doses of 1,000-1,500 mg and 800 IU, respectively -degrees of recommendation D (74) and C (14).…”
Section: General Treatment Measuresmentioning
confidence: 88%